Pengaruh Pelatihan dan Faktor Lainnya terhadap Kinerja Karyawan Divisi Finance PT X - Puriandari, Immanuela Anabel Prita; Ananda, Denta Felli (Media Bisnis, 2023)
The purpose of this research is to determine what factors can affect employee performance at Finance Department at PT X. The variables which going to be examined are Training, Compensation, Motivation and Work Discipline. The research design used in descriptive research and causality research. The sampling in the study used 77 respondents with saturated sampling techinque. This research used the multiple linear regression method with statistical data processing tools. The result showed that Training has no influence to Employee Performance, but for Compensation, Motivation and Work Discipline has influence to Employee Performance.